The Experience of Burnout in Case Loading Midwives - Young, Carolyn Mae (Auckland University of Technology, 2011)
Midwifery autonomy is epitomized in the provision of lead maternity care, a promoted and sought after consumer choice pivotal to the credibility of autonomous midwifery. The loss of experienced New Zealand midwives to autonomous practice through professional burnout has a local impact on midwifery services as well as global implications for midwives seeking autonomy of practice in other countries. This study, informed by Heidegger and Gadamer, seeks to uncover the meaning of the lived experience of midwives who self identified as having burned out in the giving of lead maternity care. Participants were purposefully selected. Data was collected through twelve interviews with New Zealand registered midwives and, with the midwives consent, through a further four interviews with their partners to generate understanding of their experience. The research showed that the reality of the weight of professional obligation in the provision of such care is largely invisible. The phenomenon of burnout is little understood within midwifery yet it seems that the nature of on call practice has a high potential for burnout. Emerging from my interpretation of the participants' stories were findings of burnout's ability to mask itself through semblance and appearance which is then further covered over by everydayness. The data is presented as first showing how burnout is masked, then how it is fuelled, and finally how the pain revealed itself within the conversation of this study. A high cost of burnout for women, midwives and midwifery was exposed. It is hoped that by revealing the extent of these midwives personal destruction and pain, and at times that of their families, a discussion around sustainable practice, realistic professional expectations and the development of more avenues of support will continue to evolve within midwifery. Within the unknowing, burnout's fires are fuelled. Only as midwives understand the phenomenon will they be more able to identify contributing factors and the need to prioritize their own well being within the midwifery working model of care.
Keywords: On-call; Burnout; Phenomenology; Heidegger; Gadamer; Midwifery